2022
DOI: 10.15376/biores.17.1.1241-1256
|View full text |Cite
|
Sign up to set email alerts
|

Biochar increases rice yield by improving root morphological and root physiological functions in heavily saline-sodic paddy soil of Northeast China

Abstract: Saline-sodic soil is one of the major threats to crop growth, production, and quality. Biochar amendment could alleviate the adverse impacts of saline-sodic stress in crops. However, the effect of biochar on root morphological, root physiological functions, and rice yield in saline-sodic paddy soil has not been studied. Here, the underlying mechanisms of positive effects in morphological characteristics and physiological functions of rice roots under heavily saline-sodic paddy soil amended with biochar were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
(54 reference statements)
0
23
0
Order By: Relevance
“…2A) and leaf relative electrical leakage (Fig. 2B), (iii) amelioration in soil physicochemical properties, which would result ultimately in promoted the uptake of water and nutrients by roots (Huang et al, 2019;Yao et al, 2021;Li et al, 2022). Thus, it is clear from the present study that peanut shell biochar can effectively ameliorate effect of osmotic stress on rice by reducing leaf ABA and MDA concentration under saline-alkali paddy eld.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…2A) and leaf relative electrical leakage (Fig. 2B), (iii) amelioration in soil physicochemical properties, which would result ultimately in promoted the uptake of water and nutrients by roots (Huang et al, 2019;Yao et al, 2021;Li et al, 2022). Thus, it is clear from the present study that peanut shell biochar can effectively ameliorate effect of osmotic stress on rice by reducing leaf ABA and MDA concentration under saline-alkali paddy eld.…”
Section: Discussionmentioning
confidence: 51%
“…In addition, Farhangi-Abriz and Torabian, (2017) found that biochar signi cantly reduced the oxidation stress through degradation the concentration of superoxide anion and hydrogen peroxide under salt stress. Biochar posed an effective effect on improving the physicochemical and biological properties of salted soils, ameliorating root environment and enhancing root absorption activity for nutrients and water (Chaganti and Crohn et al, 2015;Agbna et al, 2017;Elshaikh et al, 2018;Li et al, 2022). Moreover, the improvement in stomatal density and conductance were found after biochar application to salt-affected soils due to the decreased production of ABA (Amini et al, 2016;Ali et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is well known that Ca 2+ is conducive to the leaching of sodium ions from the soil profile, promoting the formation of soil aggregates, reducing the ESP and Na + content, and thus significantly increasing the calcium content (Table 3); therefore, biochar application can ameliorate the physical characteristics of salt-affected soils (Clark et al 2007). Third, biochar has a positive effect on the structure of salt-affected soils through soil structure-building processes, such as aggregation, thus promoting the activity of microorganisms in the root zone (Fletcher et al 2014;Kolton et al 2016;Jin et al 2018;Li et al 2022).…”
Section: Role Of Biochar In Improving Bd Tp and Ks Of Highly Saline-s...mentioning
confidence: 99%
“…The underlying explanation for the unchanged pH in the highly saline-sodic paddy field may be that (I) biochar application can increase Tp and Ks (Fig. 1), which can help leach Na + from the soil profile (Table 3) and decrease ESP (Table 5); (II) H + is dissociated from the ion exchange complex via K + , Ca 2+ , and Mg 2+ (Table 3) through peanut shell biochar (Wang et al 2015); (III) biochar significantly decreased the concentrations of CO3 2and HCO3 -(Table 4), which are main factors resulting in the high pH in saline-sodic soil; and (IV) the improvement of soil physical and chemical properties after biochar application promoted the growth of roots and increased the secretion of organic acids in roots (Li et al 2022). In addition, prior studies also showed that the initial pH of biochar may play a marked role in biocharinduced changes in the pH of salt-affected soils (Liu and Zhang 2012).…”
Section: Role Of Biochar In Balancing In the Ion Content And Improvin...mentioning
confidence: 99%
See 1 more Smart Citation